Multiple guests in a single host: interactions across symbiotic and phytopathogenic bacteria in phloem‐feeding vectors – a review. Issue 3 (25th February 2019) - Gonella, Elena; Tedeschi, Rosemarie; Crotti, Elena; Alma, Alberto
Abstract: Some pathogenic phloem‐limited bacteria are a major threat for worldwide agriculture due to the heavy economic losses caused to many high‐value crops. These disease agents – phytoplasmas, spiroplasmas, liberibacters, and Arsenophonus ‐like bacteria – are transmitted from plant to plant by phloem‐feeding Hemiptera vectors. The associations established among pathogens and vectors result in a complex network of interactions involving also the whole microbial community harboured by the insect host. Interactions among bacteria may be beneficial, competitive, or detrimental for the involved microorganisms, and can dramatically affect the insect vector competence and consequently the spread of diseases. Interference is observed among pathogen strains competing to invade the same vector specimen, causing selective acquisition or transmission. Insect bacterial endosymbionts are another pivotal element of interactions between vectors and phytopathogens, because of their central role in insect life cycles. Some symbionts, either obligate or facultative, were shown to have antagonistic effects on the colonization by plant pathogens, by producing antimicrobial substances, by stimulating the production of antimicrobial substances by insects, or by competing for host infection. In other cases, the mutual exclusion between symbiont and pathogen suggests a possible detrimental influence on phytopathogens displayed by symbiotic bacteria; conversely, examples of microbes enhancing pathogen load are available as well. Whether and how bacterial exchanges occurring in vectors affect the relationship between insects, plants, and phytopathogens is still unresolved, leaving room for many open questions concerning the significance of particular traits of these multitrophic interactions. Such complex interplays may have a serious impact on pathogen spread and control, potentially driving new strategies for the containment of important diseases. Abstract : Phloem‐limited bacterial phytopathogens, transmitted among plants by phloem‐feeding Hemiptera vectors, cause heavy losses in agriculture. Associations of pathogens and vectors form complex networks of interactions involving also the microbial community harboured by the insect host; bacterial interactions may have beneficial or detrimental influences on a vector's efficacy. How such complex interplays affect insect‐plant‐bacteria interactions is still unresolved; however, their impact on pathogen spread and control could drive new strategies for the containment of important diseases.